Ответы и объяснения

Лучший Ответ!
  • Minsk00
  • почетный грамотей
2014-01-06T02:38:51+04:00
Cos(3пи/2+а)/sin(пи-а) = sin(a)/sin(a) = 1
cos(3пи/2+а) = cos(3пи/2)cos(a)-sin(3пи/2)sin(a) = sin(a)
sin(пи-а) = sin(пи)cos(a)-cos(пи)sin(a) = sin(a)

sin(2пи-а)/cos(пи/2+а) = sin(a)/(-sin(a)) = -1
sin(2пи-а) = sin(2пи)cos(a)-cos(2пи)sin(a) = sin(a)
cos(пи/2+а) = cos(пи/2)cos(a)-sin(пи/2)sin(a) = -sin(a)

(1/2)sin(a) - sin(пи/3+а) = (1/2)sin(a) - (sin(пи/3)cos(a) +cos(пи/3)sin(a))=
= (1/2)sin(a) - (корень(3)/2)cos(a) - (1/2)sin(a) =
= - (корень(3)/2)cos(a)
sin(пи/3) = корень(3)/2; cos(пи/3) = 1/2

(корень(2)/2)sin(a) - cos(пи/4-а) =
=(корень(2)/2)sin(a) -(cos(пи/4)cos(a)+sin(пи/4)sin(a))=
= (корень(2)/2)sin(a) -(корень(2)/2)cos(a) - (корень(2)/2)sin(a) =
= -(корень(2)/2)cos(a)
cos(пи/4) =sin(пи/4) = корень(2)/2